Legal Protection for Policyholders in Motor Vehicle Insurance - Syifa Arinda; Devani Agustia; Ahmad Mufti Farid Nababan; Andhika Bayu Pranata; M Farhan Maulana Nst (ISNU Sumatera Utara, 2024)
This study examines legal protection for policyholders in motor vehicle insurance using a literature review approach. Legal protection is a crucial aspect of the relationship between insurance companies and policyholders, particularly in guaranteeing the rights that policyholders should receive as stipulated in the insurance policy. This study highlights the role of law in protecting against potential injustice arising from claim rejections or discrepancies between promised services and actual performance. This study also explores the basic principles of insurance contracts, the obligations of insurance companies, and the rights of policyholders. Furthermore, it discusses the forms of dispute resolution available when disputes arise between policyholders and insurance companies, both through litigation and non-litigation mechanisms. The results of this literature review indicate that legal protection for policyholders is highly dependent on the clarity of the insurance contract, the understanding of the law by both parties, and the effectiveness of dispute resolution institutions in upholding justice. Therefore, it is necessary to improve legal education for policyholders and strengthen regulations in insurance practices to create a fair, transparent, and balanced relationship between insurance companies and policyholders.